PERDAGANGAN LINTAS BATAS DI JAGOI BABANG - SERIKIN WILAYAH PERBATASAN INDONESIA – MALAYSIA DALAM PERSPEKTIF HUKUM INTERNASIONAL - Desi Yuniarti (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2019)
As an area bordering Sarawak, Malaysia, quite a lot of residents of West Kalimantan (West Kalimantan) work abroad, including trading through official and unofficial border gates. The most crowded route for informal traders from Indonesia to enter Sarawak is the Jagoi Babang border (Bengkayang Regency) and Serikin (Sarawak). Every weekend (Saturday and Sunday), quite a lot of Indonesian traders trade in Serikin Sarawak. This cross-border trading activity is very risky to be banned at any time by the Malaysian government while cross-border traders from Indonesia are very dependent on activities in Serikin Market.